Codex Amiatinus of the Latin Vulgate Bible and Its Birthplace - White, H. J. (Analecta Gorgiana, 2006)
White takes the reader through a historical puzzle revolving around the date of the Vulgate manuscript Codex Amiatinus. He demonstrates that the manuscript falls in the eighth century and traces its origins to Italy